Beyond the Golden Hour: Treating Acute Stroke in the Platinum 30 Minutes. Issue 8 (12th May 2022) - Randhawa, Anantbir S.; Pariona-Vargas, Fatima; Starkman, Sidney; Sanossian, Nerses; Liebeskind, David S.; Avila, Gilda; Stratton, Samuel; Gornbein, Jeffrey; Sharma, Latisha; Restrepo-Jimenez, Lucas; Valdes-Sueiras, Miguel; Kim-Tenser, May; et al.
Abstract : Background: To emphasize treatment speed for time-sensitive conditions, emergency medicine has developed not only the concept of the golden hour, but also the platinum half-hour. Patients with acute stroke treated within the first half-hour of onset have not been previously characterized. Methods: In this cohort study, we analyzed patients enrolled in the FAST-MAG (Field Administration of Stroke Therapy–Magnesium) trial, testing paramedic prehospital start of neuroprotective agent ≤2 hours of onset. The features of all acute cerebral ischemia, and intracranial hemorrhage patients with treatment starting at ≤30 m of last known well were compared with later-treated patients. Results: Among 1680 patients, 203 (12.1%) received study agents within 30 minutes of last known well. Among platinum half-hour patients, median onset-to-treatment time was 28 minutes (interquartile range, 25–30), and final diagnoses were acute cerebral ischemia in 71.8% (ischemic stroke, 61.5%, TIA 10.3%); intracranial hemorrhage in 26.1%; and mimic in 2.5%. Clinical features among platinum half-hour patients were largely similar to later-treated patients and included age 69 (interquartile range, 57–79), 44.8% women, prehospital Los Angeles Motor Scale median 4 (3–5), and early-postarrival National Institutes of Health Stroke Scale deficit 8 (interquartile range, 3–18). Platinum half-hour acute cerebral ischemia patients did have more severe prehospital motor deficits and younger age; platinum half-hour intracranial hemorrhage patients had more severe motor deficits, were more often female, and less often of Hispanic ethnicity. Outcomes at 3 m in platinum half-hour patients were comparable to later-treated patients and included freedom-from-disability (modified Rankin Scale score, 0–1) in 35.5%, functional independence (modified Rankin Scale score, 0–2) in 53.2%, and mortality in 17.7%. Conclusions: Prehospital initiation permits treatment start within the platinum half-hour after last known well in a substantial proportion of acute ischemic and hemorrhagic stroke patients, accounting for more than 1 in 10 enrolled in a multicenter trial. Hyperacute platinum half-hour patients were largely similar to later-treated patients and are an attainable target for treatment in prehospital stroke trials.